Excision of an atypical case of palatal bone exostosis: a case report. - Raldi, Fernando V (2008)
Bone exostosis has long been described in the literature, appearing in most cases as a torus palatinus or mandibularis. These two variations are relatively common and affect approximately 30% of the world's population. Incidence is even higher when human skulls are examined post mortem, indicating that in some cases the exostosis is small and cannot be seen under the soft tissue. Removal of an exostosis is usually associated with the construction of a prothesis, but in rare cases such as the present, the lesion enlarges enough to affect speech and feeding. Few studies have reported the removal of such a large exostosis, and all were conducted in a hospital environment. In this case, complete removal was successfully conducted in an ambulatory clinic under local anesthesia.